A Criminological Perspective on Cyber-crimes and Theories of Criminal Behaviour in Cyberspace: Exploring the Nature and Behavior of Cyber-criminals (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cyber world is the combination of computers and other communication convergence Technologies. No doubt the techno world has raised the job opportunities and the platforms to the youngsters to grow professionally as well as economically but at the same time it raises complex problems for traditional laws which are now to be applied in superhighway with new spectacle because these laws are not adequate in cyberspace always. Cyberspace has no specific location which is another problem in contemporary legal system. Cyber world is the world without specific boundaries where people with a keyboard and mouse by single click can visit whole world, can speak with any one they wish, can see any one they wish, even thousands of miles away, they can have online discussion with each other, exchange their views, sell and purchase things, access banking facilities, create information and exchange information online. For improving the legal system and to control the cyber-crimes it is necessary to seek the insight understanding of nature and behavior of the criminal. The theories of Criminology can help to make it possible to some extent to put hold on cyber-crimes.